Transformation of Riyadlul Jannah Mosque in Gedok Hamlet Into an Educational Center (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The lack of motivation to recite the Koran in society is one of the problems Muslims face inIndonesia, one of which occurred in Gedok Hamlet, Argosari Village, Senduro District,Lumajang Regency. Based on the data obtained at TPQ Riyadlul Jannah Dusun Gedok,several problems were found related to studying the Koran. This community service activityaims to increase student motivation in participating in recitation activities at TPQ RiyadlulJannah with a religious activity approach that is held regularly at the Riyadlul JannahMosque. In addition, this activity is also carried out by inviting leaders and the public to carryout Laylatul Ijtima's activities, which consist of several agenda arrangements such asistighosah, reading Surah Yasin, and Diba'i, which are held once a week. Lailatul Ijtima is areligious event held at night to gather Muslims and carry out various activities of worship,recitation, and religious studies. The Khotmil Qur'an activity is carried out by reading theKoran verses from the surah's beginning to the end in the order in the Mushaf of the Qur'anat the Riyadlul Jannah Mosque. Based on community empowerment activities in thereligious field, the leaders and community of Gedok Hamlet, especially the parents,responded well.